MICRO-CRYSTAL STRUCTURE OF 57Fe15Cr25Ni0.32Mn0.96Si AUSTENITE STEEL AFTER 850°C-5H TEMPERATURE-QUENCHING TREATMENTS FOR HIGH TEMPERATURE MATERIAL APPLICATIONS - Parikin Parikin; Rudi Rudi; Sumaryo Sumaryo; S Ahda (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2018)
MICRO-CRYSTAL STRUCTURE OF 57Fe15Cr25Ni0.32Mn0.96Si AUSTENITE STEEL AFTER 850°C-5H TEMPERATURE-QUENCHING TREATMENTS FOR HIGH TEMPERATURE MATERIAL APPLICATIONS. A serial austenite stainless steel, namely A2-type, has been synthesized by using casting technique at temperature more than 1250 °C in the induction furnace that used an electromagnetic inductive-thermal system. The steel is dedicated for structural component material in multi-purpose applications such as in high-temperature operating environments. So, the material must be resistant to mechanical loads, high temperature, corrosion and irradiation. In order to increase the strength of materials, temperature-quenching treatments are required in some cooling media. Mineral element was extracted from crude ores of Indonesian mines and commercial scrap materials, i.e: ferro scrap, ferro chrome, nickel, manganese, and ferro silicon; all of them in granular shape were prepared to alloy the steel. Titanium was not added to this austenite low carbon steel. The OES-chemical composition in %wt of the materials is 57%Fe, 15%Cr, 25%Ni, 0.34%C and less than 0.1% of impurities that comprised of: titanium, phosphor, copper, niobium and sulphur elements in the steel. X-ray diffraction pattern shows that ascast material had an fcc crystal structure with lattice parameter of 3.632 Å. Meanwhile, two of samples, i.e: annealing and oil quench, have strictly similar lattice parameter to that of air (normalizing) quench (3.580 Å). On the other hand, the lattice parameter of water quenched samples has a slightly lower lattice parameter than the ascast lattice , i.e. 3.587 Å. The peak shift of (111) and (200) -plane in the diffraction profile, is very significant, approximately 0.63 degrees between ascast sample and the last two samples. Ascast microstructure reveals that the austenite phase grains look large and describe an undeformed structure, with an average grain size of about 6 mm, while the annealed sample was larger. Air- and oil- quenched sample microstructures showed a fine grain which was very different to water quenched sample microstructure that showed a coarse grain. The viscousity (h) of the quenching medium had an important role in the formation of grain boundary, because the rate of decreasing temperature was heavily influenced by the diffusion of heat from the high to low temperature spaces.